POU1F1 transcription factor induces metabolic reprogramming and breast cancer progression via LDHA regulation - Martínez-Ordoñez, Anxo (Oncogene, 2021)
Metabolic reprogramming is considered hallmarks of cancer. Aerobic glycolysis in tumors cells has been well-known for almost a century, but specific factors that regulate lactate generation and the effects of lactate in both cancer cells and stroma are not yet well understood. In the present study using breast cancer cell lines, human primary cultures of breast tumors, and immune deficient murine models, we demonstrate that the POU1F1 transcription factor is functionally and clinically related to both metabolic reprogramming in breast cancer cells and fibroblasts activation. Mechanistically, we demonstrate that POU1F1 transcriptionally regulates the lactate dehydrogenase A (LDHA) gene. LDHA catalyzes pyruvate into lactate instead of leading into the tricarboxylic acid cycle. Lactate increases breast cancer cell proliferation, migration, and invasion. In addition, it activates normal-associated fibroblasts (NAFs) into cancer-associated fibroblasts (CAFs). Conversely, LDHA knockdown in breast cancer cells that overexpress POU1F1 decreases tumor volume and [(18)F]FDG uptake in tumor xenografts of mice. Clinically, POU1F1 and LDHA expression correlate with relapse- and metastasis-free survival. Our data indicate that POU1F1 induces a metabolic reprogramming through LDHA regulation in human breast tumor cells, modifying the phenotype of both cancer cells and fibroblasts to promote cancer progression.